Shortening Supply Chains for Fruit and Vegetable Vendors in Bogota - McKenzie, David (World Bank, Washington, DC, 2019)
The latest note examines the impact of a social enterprise's attempts to shorten the supply chain between farmers and small retail stores in Bogota, an idea that was one of the winners of the SME ideas competition. The small retail stores that are prevalent on many street corners in developing countries face very different supply chains for different products. On one hand, multinational suppliers of branded non-perishable products have amazingly efficient supply chains that result in store-door delivery to even the most remote places. In contrast, the fresh fruit and vegetables they sell are part of what are typically much less efficient supply chains, that often end in centralized wholesale markets, requiring substantial travel time and costs for retail store vendors, and increased food costs for the urban poor. This is the case in Bogota, where the typical store owner gets up at 4:30am each morning, and spends an average of 2 hours travelling to, around, and back from the central market of Corabastos in order to buy fruits and vegetables.